Neuron-specific activation of necroptosis signaling in multiple sclerosis cortical grey matter - Picon, Carmen (Acta Neuropathol, 2021)
Sustained exposure to pro-inflammatory cytokines in the leptomeninges is thought to play a major role in the pathogenetic mechanisms leading to cortical pathology in multiple sclerosis (MS). Although the molecular mechanisms underlying neurodegeneration in the grey matter remain unclear, several lines of evidence suggest a prominent role for tumour necrosis factor (TNF). Using cortical grey matter tissue blocks from post-mortem brains from 28 secondary progressive MS subjects and ten non-neurological controls, we describe an increase in expression of multiple steps in the TNF/TNF receptor 1 signaling pathway leading to necroptosis, including the key proteins TNFR1, FADD, RIPK1, RIPK3 and MLKL. Activation of this pathway was indicated by the phosphorylation of RIPK3 and MLKL and the formation of protein oligomers characteristic of necrosomes. In contrast, caspase-8 dependent apoptotic signaling was decreased. Upregulation of necroptotic signaling occurred predominantly in macroneurons in cortical layers II–III, with little expression in other cell types. The presence of activated necroptotic proteins in neurons was increased in MS cases with prominent meningeal inflammation, with a 30-fold increase in phosphoMLKL+ neurons in layers I–III. The density of phosphoMLKL+ neurons correlated inversely with age at death, age at progression and disease duration. In vivo induction of chronically elevated TNF and INFγ levels in the CSF in a rat model via lentiviral transduction in the meninges, triggered inflammation and neurodegeneration in the underlying cortical grey matter that was associated with increased neuronal expression of TNFR1 and activated necroptotic signaling proteins. Exposure of cultured primary rat cortical neurons to TNF induced necroptosis when apoptosis was inhibited. Our data suggest that neurons in the MS cortex are dying via TNF/TNFR1 stimulated necroptosis rather than apoptosis, possibly initiated in part by chronic meningeal inflammation. Neuronal necroptosis represents a pathogenetic mechanism that is amenable to therapeutic intervention at several points in the signaling pathway. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s00401-021-02274-7.